X-ray inspection systems with sandwich radiation detectors: A survey - Udod, Victor A. (Recent developments in the field of non-destructive testing, safety and materials science)
At the present time, scanning systems for digital radiography (SSDR) are often used for inspection, as well as for defectoscopy and diagnostics of materials and products. The range of tasks solved on the basis of SSDR is very wide and includes, in particular, the tasks of detecting explosive, toxic and radioactive substances, as well as explosive devices, all types of weapons and damaging elements For the recognition of materials in the SSDR, intended for inspection control in order to ensure the safety of transportation and suppress attempts to smuggle illegal items, the method of dual energies (MDE) is widely used today. This method makes it possible to simultaneously evaluate two parameters of the object of control (OC) – the effective atomic number of the OC material and its mass thickness. This paper reports the state of X-ray inspection systems with sandwich radiation detectors. Besides, this paper presents description of dual energy method with using x-ray sandwich detectors in inspection control system for material recognition.